Kontakty międzyetniczne w sferze regionalnego toponimikonu (na materiale obwodu włodzimirskiego) - Lukyanova, Ekaterina (Acta Polono-Ruthenica, 2012)
The article deals with the question of the interethnic relations reflection on the example of ethnic toponymy. On the basis of the analyzing the toponymical system of Vladimir region the author established the following stratas of geographic names which characterize interethnic rela- tions in different periods of the denoted territory development: substrate toponymy which charac- terizes the period of contacts between the Slavs and Finno-Ugric tribes and toponyms formed of nationality names inhabited denoted geographical locations in the certain period. Ethnic toponymy actualizes for the people«s collective important point self foreign.